Akomodasi Komunikasi Antarbudaya Santri dalam Menghadapi Ambivalensi Nilai Global di Ruang Digital - Alfarizi Cahya Maulana; Fawaizul Umam; Siti Raudhatul Jannah (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
The development of digital space has transformed the communication patterns of santri, particularly in accessing religious knowledge, constructing identity, and responding to global values. Santri no longer engage with pesantren values solely through classical Islamic texts, the guidance of kyai, and Islamic educational traditions; they now do so also through social media, visual content, digital algorithms, and artificial intelligence. This study aims to analyze the intercultural communication accommodation strategies of santri in facing the ambivalence of global values in digital space. This study adopts a library research design with a qualitative-descriptive approach. Data were obtained through a review of journal articles, academic literature, intercultural communication theories, pesantren regulations, and relevant documents on pesantren, santri, digital da'wah, and global culture. The data were analyzed using thematic content analysis based on Communication Accommodation Theory, identity negotiation theory, and intercultural communication perspectives. The findings show that santri respond to the ambivalence of global values through value selection, communication convergence, identity divergence, and the internalization of digital adab. This study concludes that santri are active communication actors who adapt, filter, and affirm their Islamic identity in digital space, while pesantren function as value mediators between Islamic tradition and global digital culture.